Tejano West Texas - De León, Arnoldo, 1945- (Book collections on Project MUSE., 2015)
Featuring a side of Tejano history too often neglected, author Arnoldo De León shows that people of Spanish-Mexican descent were not passive players in or, worse, absent from West Texas history but instead were active agents at the center of it. The collection of essays in Tejano West Texas-many never before published-will correct decades of historiographical oversight by emphasizing the centrality of the Mexican American experience in the history of the region. De León, a true dean of Tejano history, showcases the continued presence and contribution of Mexican Americans to West Texas. This co.